Ocular Motor Abnormalities in Anti-IgLON5 Disease - Macher, Stefan; Milenkovic, Ivan; Zrzavy, Tobias; Höftberger, Romana; Seidel, Stefan; Berger-Sieczkowski, Evelyn; Berger, Thomas; Rommer, Paulus S.; Wiest, Gerald (Frontiers in Immunology, 2021)
Objective Anti-IgLON5 disease forms an interface between neuroinflammation and neurodegeneration and includes clinical phenotypes that are often similar to those of neurodegenerative diseases. An early diagnosis of patients with anti-IgLON5 disease and differentiation from neurodegenerative diseases is necessary and may have therapeutic implications. Methods: We investigated oculomotor function as a differentiating factor between anti-IgLON5 disease and neurodegenerative disorders. Ocular motor and vestibular function were examined in four patients suffering from anti-IgLON5 disease using video-oculography (VOG) and a computer-controlled rotational chair system (sampling rate 60 Hz) and compared the data with those from ten age matched patients suffering from progressive supranuclear palsy (PSP) and healthy controls (CON). Results: Patients suffering from anti-IgLON5 disease differed from PSP most strikingly in terms of saccade velocity and accuracy, the presence of square wave jerks (SWJ) (anti-IgLON5 0/4 vs. PSP 9/10) and the clinical finding of supranuclear gaze palsy (anti-IgLON5 1/4). The presence of nystagmus, analysis of smooth pursuit eye movements, VOR and VOR suppression was reliable to differentiate between the two disease entities. Clear differences in all parameters, although not always significant, were found between all patients and CON. Discussion: We conclude that the use of VOG as a tool for clinical neurological assessment can be helpful in differentiating between patients with PSP and patients with anti-IgLON5 disease. VOG could have particular value in patients with suspected PSP and lack of typical Parkinson’s characteristics. Future studies are indispensable to assess the potential of oculomotor function as a biomarker in anti-IgLON5 disease.